Screening of Locally Isolated Actinomycetes and Endophytic Fungi for Production of Bioactive Compounds - Lim, Jeffrey Seng Heng (2006)
Isolation of actinomycetes were done using Humic acid B-vitamins Agar (HVA) while endophytic fungi were from Potato Dextrose Agar (PDA). Isolated strains were then subjected to enzymatic and also antimicrobial testing. Positive strains for antimicrobial testing were then subjected to carbon source utilization testing and viewed under microscope to determine their spores morphology. From the enzymatic test conducted for actinomycetes, 110 isolates showed positive result for cellulase activity, 107 for xylanase activity and 22 for mannanase activity. Fifteen isolates of endophytic fungi have the ability to degrade cellulose, 28 of the isolates were able to degrade xylan and 12 isolates have the potential to degrade mannan. Thirteen isolates of actinomycetes showed positive result towards the 5 strains of pathogenic microorganisms with the highest on Yersinia enterocolitica. While test done using endophytic fungi showed only 1 isolate with antimicrobial property toward Xanthomonas campestris. Biolog test was done to determine the metabolite diversity of each actinomycetes. Twelve of the 13 isolates of actinomycetes were identified to be from the genus of Streptomyces by observing their spore arrangement and 1 of the isolate could not be identified. Biolog test could not be done on the endophytes fungi strain 13 because this strain does not produce spores.Through microscopic imaging the identity of the endophytes fungi isolate also could not be determined. Actinomycetes isolate number 200 was further identified by targeting its 16S rRNA gene. By using this technique Actinomycetes isolate number 200 was confirmed to be from the genus Streptomyces.